Factors affecting customers intention towards online pharmacies in Indonesian market - Ferawaty, Ferawaty; Antonio, Wakky; Anggraeni, Adilla (Institute of Advanced Engineering and Science, 2024)
Online pharmacies are a promising business model for promoting online sales of medicines. The purpose of this study is to investigate how technology acceptance model (TAM) variables (perceived ease of use and perceived usefulness), perceived trust, perceived performance risk, and perceived physical risk influence customers' intention to use online pharmacy. A questionnaire survey was used to collect data for the planned study. The results showed that perception of trust is a critical factor influencing costomers intention to use an online pharmacy. The reluctance of customers to buy medicines, categorized as risk, through online pharmacies which was originally thought to be a determining factor, has no impact if customer trust in online pharmacy has been formed. This study has several relevances for advancing online pharmacy promotion including the importances of user-friendly and benefits provided by online pharmacies provider. It is very important how online pharmacies providers can increase customers trust in terms of legality, quality and security of personal data.